Justification of the choice of public transport service type on the route - Skirkouski, S. V.; Sedziukevich, U. M.; Svichynska, O. V.; Скірковський, С. В.; Седюкевич, В. М.; Свічинська, О. В. (Харківський національний автомобільно-дорожній університет, 2021)
Problem. Currently, there exist two main types of service on public transport routes – headway-based and timetable-based. They differ by the frequency of service at the stops and by the information available for passengers. The required frequency of service significantly affects transport operator costs and passenger travel time which, in turn, influences the cost for a passenger. One of the ways to reduce costs for both parties of the transportation process is to make a reasonable choice of the type of service or switch between the types during the day depending on the passenger flow volume. Goal. In the paper, to justify the choice of between the types of service, the cost of public transport vehicles operation and the losses of passenger travel times are taken into account. Methodology. The developed way of making a choice about the type of service allows increasing the efficiency of urban public transport due to reducing the passenger waiting time by switching from the headway-based service in rush hours to timetable-based service in the periods of passenger flow volume decline. Results. The relationship allowing making a decision about the type of service on the route is developed. It allows to correctly introduce the type of service which will ensure the balance between the transport operator and passenger costs. Originality. The developed approach to make a decision on the type of service allows reducing the passenger waiting time by switching from headway-based service in rush hours to the timetable-based service in the periods of decline in passenger flow volume during the day. Practical value. The results of the research based on the survey data allowed estimating the numerical value of the headway at which it is expedient to switch to the timetable-based service.
Обґрунтування вибору форми надання послуг громадського транспорту на маршруті
Keywords: passenger transportation; public transport; type of service; headway; waiting time; пасажирські перевезення; громадський транспорт; форма обслуговування; інтервал руху; час очікування; 656.072; 10.30977/AT.2219-8342.2021.48.0.79